Genotoxicity and Cytotoxicity Induced in Zygophyllum fabago by Low Pb Doses Depends on the Population’s Redox Plasticity - Antonio López-Orenes (MDPI AG, 2021)
Lead (Pb) soil contamination remains a major ecological challenge. Zygophyllum fabago is a candidate for the Pb phytostabilisation of mining tailings; nevertheless, the cytogenotoxic effects of low doses of Pb on this species are still unknown. Therefore, Z. fabago seeds collected from non-mining (NM) and mining (M) areas were exposed to 0, 5 and 20 µM Pb for four weeks, after which seedling growth, Pb cytogenotoxic effects and redox status were analyzed. The data revealed that Pb did not affect seedling growth in M populations, in contrast to the NM population. Cell cycle progression delay/arrest was detected in both NM and M seedlings, mostly in the roots. DNA damage (DNAd) was induced by Pb, particularly in NM seedlings. In contrast, M populations, which showed a higher Pb content, exhibited lower levels of DNAd and protein oxidation, together with higher levels of antioxidants. Upon Pb exposure, reduced glutathione (GSH) and non-protein thiols were upregulated in shoots and were unaffected/decreased in roots from the NM population, whereas M populations maintained higher levels of flavanols and hydroxycinnamic acids in shoots and triggered GSH in roots and shoots. These differential organ-specific mechanisms seem to be a competitive strategy that allows M populations to overcome Pb toxicity, contrarily to NM, thus stressing the importance of seed provenance in phytostabilisation programs.